„Język polski jest tak bogaty, giętka jest nasza mowa!” Podstawowa Organizacja Partyjna Oddziału Warszawskiego Związku Literatów Polskich i jej stosunek do polityki kierownictwa partyjnego w latach 1956–1970 - Rokicki, Konrad (Pamięć i Sprawiedliwość, 2012)
The Basic Party Cell (POP) at the Warsaw Branch, was the Polish United Workers’ Party’s (PZPR’s) strongest party unit in the Polish Writers’ Association (ZLP). In Stalinist years, it was used to control and indoctrinate the community of writers. After the political “thaw” it was affected by very strong reformist tendencies, called “revisionist” by communist authorities. That was the difference between it and other PZPR’s cells in ZLP’s branches. Also, POP OW ZLP due to its numerosity and connections of some its members with the party leadership, exerted real infl uence on ZLP’s activities and on the relations between writers and the communist party. Nonetheless, internal divisions in the organisation were very deep. In addition to “revisionists”, the POP was also composed of a group of writers completely subordinated to the party’s instructions. Within the POP OW ZLP a discussion was held on the scope of writers’ duties, resulting from the fact of membership in PZPR. Should restrictions of free expression be accepted? Can writers-party members participate in creating the cultural policy, or should they only implement its guidelines? Are there perhaps any false intermediaries in the relations between POP, and the party leadership? The authorities’ actions towards communities of creators – mainly imposing restrictions of freedom of speech – promptly triggered protests, also of a part of the members of POP OW ZLP. In the 14 years of Gomułka’s rule, the highest emotions were provoked by the liquidation of the monthly „Europa” and founding of the Warsaw weekly „Kultura”, the dispute over the letter of 34 and the counterletter of POP OW ZLP, the expelling of Leszek Kołakowski from PZPR, and the March campaign. In this period, some writers-party members, ignoring the risk of disfavour – left the party’s ranks; while others remained in the organisation for a long time, forming an informal opposi- tion (“dissent within the party”), yet others remained members only in formal terms, the group of orthodox communists rapidly diminishing. In the late 1960s, when the anti-intelligentsia phobia among the party’s leadership became evident for everybody, it was hard to find any big names among the members of POP OW ZLP. The organisation became uniform in terms of ideology, but devoid of authority and despite the opposition’s resignation from struggle, it proved incapable of leading the community of writers. The fortunes of POP OW ZLP seem to be a good example of ideological reconsiderations and changing attitudes within the communist party’s intelligentsia towards the policies of Gomułka.